Development of Creative Economy Educational Tour Pocket Books in Semarang City - Indarsih, Fitria Retno; Widayani, Sus; Anis, Samsudin (Universitas Negeri Semarang, 2021)
The development of tourism sector in Semarang city has been established by Creative Economic Agency (BEKRAF) as one of the creative city in the field of culinary, fashion, and crafts. But not many people know about the existance of some reference books and the absence of a guide book about creative economy educational tourism affect the tourists’ interests towards creative economy educational tourism in the field of culinary in Semarang city. This thing became the purpose of the study to discuss some problems that intended to be disclosed are: 1) To develop a creative economy educational tour pocket book; 2) To analyze the feasibility of a creative economy educational tour pocket book; 3) To analyze the practicality of a creative economy educational tour pocket book to tourists, and 4) To analyze the effectiveness of a creative economy educational tour pocket book to interest tourists. This research used RD method (Research and Development) which refers to model development of ADDIE (Analysis, Design, Development, Implementation, Evaluation). Population and Sample is obtained all travelers who travel in Semarang city. Based on assessment results, it can be found that validator expert obtained an average score of 4,58 included in the category of very decent, material experts got average score of 4,72 included in the category of very decent, assessment result done by the respondents that is focused on practicality of a pocket book is in the category of overral positive position with average score of 97,5%, and the questionnaire results of tourists’ interests to the creative economy educational tour pocket book categorized as an effective thing because it reaches 4,26%. This shows that creative economy educational tour pocket book can affect the tourists’ interests.